An Observation of Classroom Assessment Practices Among Lecturers in Selected Malaysian Higher Learning Institutions - Singh, Charanjit Kaur Swaran; Lebar, Othman; Kepol, Napisah; Abdul Rahman, Rafiah; Muhammad Mukhtar, Kurotol Aini (Universiti Utara Malaysia Press, 2017)
Purpose - The study was aimed at exploring and analysing the current assessment practices of lecturers in selected Malaysian higher learning institution classrooms. The focus was the different modes of assessment used in the classroom and to make recommendations on using a variety of assessment modes that would be well-aligned with the intended learning outcomes.